Equilibrium processes in biomedical data analysis: the Wright–Fisher model - Koroliouk, D.; Koroliuk, V.S.; Rosato, N. (Кибернетика и системный анализ, 2014)
The biological process of cooperative interaction with equilibrium state will be described as a model of binary statistical experiments with Wright–Fisher normalization, which sets the concentration of a certain characteristic. Such mathematical model is supposed to have a property of persistent regression which means that all current elementary transitions depend on the mean concentration of the said characteristics in the previous state. Equilibrium state of the model is expressed in the terms of the regression function, given by a cubic parabola with three real roots. We construct stochastic approximation of the model by autoregressive process with normal disturbances. Such approach was developed for effective and calculable mathematical description of dynamic concentration for experiment planning, parameters evaluation and hypotheses verification of mechanism of action. Біологічний процес кооперативної взаємодії з рівноважним станом описано як модель бінарних статистичних експериментів з нормалізацією Райта–Фішера, що встановлює концентрацію певної ознаки. Така математична модель, як передбачається, має властивість наполегливої регресії, яка означає, що всі поточні елементарні переходи залежать від середньої концентрації зазначеної ознаки в попередньому стані. Рівноважний стан моделі виражено в термінах функції регресії у вигляді кубічної параболи з трьома дійсними коренями. Побудовано стохастичну апроксимацію моделі процесом авторегресії з нормальними збуреннями. Такий підхід розроблено для конструктивного математичного опису динамічної концентрації для планування експерименту, оцінки параметрів і перевірки гіпотез механізму дії.